Templated synthesis of novel molecules and materials using 1,4-disubstituted-1,2,3-triazole supramolecular building blocks - MCCARNEY, EOIN (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
This thesis, entitled "Templated synthesis of novel molecules and materials using 1,4-disubstituted-1,2,3-triazole supramolecular building blocks", describes the facile synthetic modification of the 1,4-disubstituted-1,2,3-triazole motif in the development and characterisation of new ligands and their various discrete and polymeric supramolecular systems. Chapter 1 introduces the most recent advances from the literature involving the supramolecular chemistry of the 1,4-disubstituted-1,2,3-triazole. Particular attention is paid to 2,6-bis(1,2,3-triazol-4-yl)pyridine and 2-(1,2,3-triazol-4-yl)pyridine moieties. The applications of these motifs in the formation of various functional systems such as metallo-supramolecular gels, porous coordination polymers and mechanically interlocked systems is summarised. Chapter 2 details the successful synthetic modification of the 2,6-bis(1,2,3-triazol-4-yl)pyridine core and characterisation of several new metal-chelating systems. Chapter 3 describes the formation of several f-metal templated supramolecular systems using the newly synthesised range of ligands. This study is extended to investigating the formation of highly luminescent metallo-supramolecular gels and the study of their interesting healable properties. Chapter 4 focuses on the d-metal templated synthesis of several coordination polymer materials using the divergent metal binding ability of one of the newly developed ligand systems. The porous systems developed are investigated for the uptake of specific guests in the development of luminescent materials. Chapter 5 discusses the pre-organisation ability of several 2,6-bis(1,2,3-triazol-4-yl)pyridine systems for the formation of self-templating mechanically interlocked molecules. Chapter 6 presents a coordination chemistry study into the d-metal binding selectivity of a subtly unsymmetric 1,4-disubstituted-1,2,3-triazole ligand containing two possible coordination sites. Chapter 7 provides detailed experimental procedures. References are provided in Chapter 8 and supplementary data and spectra are presented in several Appendices.
APPROVED
Keywords: 1,4-disubstituted-1,2,3-triazole; Templated; supramolecular; Gels; MOF; PCP; catenane; coordination complex; functional